Immunopathogenesis and Virus–Host Interactions of Enterovirus 71 in Patients with Hand, Foot and Mouth Disease - Cox, Jonathan A.; Hiscox, Julian A.; Solomon, Tom; Ooi, Mong-How; Ng, Lisa F. P. (Frontiers in Microbiology, 2017)
Enterovirus 71 (EV71) is a global infectious disease that affects millions of people. The virus is the main etiological agent for hand, foot, and mouth disease with outbreaks and epidemics being reported globally. Infection can cause severe neurological, cardiac, and respiratory problems in children under the age of 5. Despite on-going efforts, little is known about the pathogenesis of EV71, how the host immune system responds to the virus and the molecular mechanisms behind these responses. Moreover, current animal models remain limited, because they do not recapitulate similar disease patterns and symptoms observed in humans. In this review the role of the host–viral interactions of EV71 are discussed together with the various models available to examine: how EV71 utilizes its proteins to cleave host factors and proteins, aiding virus replication; how EV71 uses its own viral proteins to disrupt host immune responses and aid in its immune evasion. These discoveries along with others, such as the EV71 crystal structure, have provided possible targets for treatment and drug interventions.